DNA Methylation of the Serotonin Transporter Gene in Peripheral Cells and Stress-Related Changes in Hippocampal Volume: A Study in Depressed Patients and Healthy Controls - Booij, Linda; Szyf, Moshe; Carballedo, Angela; Frey, Eva-Maria; Morris, Derek; Dymov, Sergiy; Vaisheva, Farida; Ly, Victoria; Fahey, Ciara; Meaney, James; Gill, Michael; Frodl, Thomas (PLOS ONE, 2015)
Serotonin plays an important role in the etiology of depression. Serotonin is also crucial for brain development. For instance, animal studies have demonstrated that early disruptions in the serotonin system affect brain development and emotion regulation in later life. A plausible explanation is that environmental stressors reprogram the serotonin system through epigenetic processes by altering serotonin system gene expression. This in turn may affect brain development, including the hippocampus, a region with dense serotonergic innervations and important in stress-regulation. The aim of this study was to test whether greater DNA methylation in specific CpG sites at the serotonin transporter promoter in peripheral cells is associated with childhood trauma, depression, and smaller hippocampal volume. We were particularly interested in those CpG sites whose state of methylation in peripheral cells had previously been associated with in vivo measures of brain serotonin synthesis. Thirty-three adults with Major Depressive Disorder (MDD) (23 females) and 36 matched healthy controls (21 females) were included in the study. Depressive symptoms, childhood trauma, and high-resolution structural MRI for hippocampal volume were assessed. Site-specific serotonin transporter methylation was assessed using pyrosequencing. Childhood trauma, being male, and smaller hippocampal volume were independently associated with greater peripheral serotonin transporter methylation. Greater serotonin transporter methylation in the depressed group was observed only in SSRI-treated patients. These results suggest that serotonin transporter methylation may be involved in physiological gene-environment interaction in the development of stress-related brain alterations. The results provide some indications that site-specific serotonin transporter methylation may be a biomarker for serotonin-associated stress-related psychopathology.